2021
DOI: 10.1021/acs.langmuir.0c02408
|View full text |Cite
|
Sign up to set email alerts
|

Dual Stimuli-Responsive Pickering Emulsions from Novel Magnetic Hydroxyapatite Nanoparticles and Their Characterization Using a Microfluidic Platform

Abstract: Stimuli-responsive emulsifiers have emerged as a class of smart agents that can permit regulated stabilization and destabilization of emulsions, which is essential for food, cosmetic, pharmaceutical, and petroleum industries. Here, we report the synthesis of novel “smart” hydroxyapatite (HaP) magnetic nanoparticles and their corresponding stimuli-responsive Pickering emulsions and explore their movement under confined spaces using a microfluidic platform. Pickering emulsions prepared with our magnetic stearic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…We think that the smart tunability of the Pickering emulsion opens a new avenue for integrating the in situ catalyst recovery and product separation with the chemical reaction. Analogy to the concept of the thermoregulated phase transfer catalysis developed by Jin et al., [143] where a thermal response triggers the water‐soluble catalysts migrating to the organic phase to catalyze a reaction, building the smart emulsion system which responses to the external controllable stimuli such as magnetic field, [120,144] pH, [92,115,144b,145] CO 2 , [117–118,120] heat, [122,146] and light [123,132] was demonstrated to effectively switch the type and the stability of the Pickering emulsion. The stimulus‐responsive Pickering emulsion was proven to be the promising strategy to boost the catalyst/product recovery and the construction of the corresponding functional emulsifiers is becoming a front‐burner issue in the field, requiring the in‐depth study.…”
Section: Discussionmentioning
confidence: 99%
“…We think that the smart tunability of the Pickering emulsion opens a new avenue for integrating the in situ catalyst recovery and product separation with the chemical reaction. Analogy to the concept of the thermoregulated phase transfer catalysis developed by Jin et al., [143] where a thermal response triggers the water‐soluble catalysts migrating to the organic phase to catalyze a reaction, building the smart emulsion system which responses to the external controllable stimuli such as magnetic field, [120,144] pH, [92,115,144b,145] CO 2 , [117–118,120] heat, [122,146] and light [123,132] was demonstrated to effectively switch the type and the stability of the Pickering emulsion. The stimulus‐responsive Pickering emulsion was proven to be the promising strategy to boost the catalyst/product recovery and the construction of the corresponding functional emulsifiers is becoming a front‐burner issue in the field, requiring the in‐depth study.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that cell migration was inversely proportional to HAP concentration [ 97 ]. Along the same lines, the bibliography offers original studies covering different objectives that are worth consulting [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Application Of Modern Computational Methods In Hap Based Materialsmentioning
confidence: 99%
“…Pickering emulsions responding to dual triggers such as temperature–pH [ 29 ], CO 2 –temperature [ 16 ], CO 2 –magnetism [ 14 , 30 ], and redox–magnetism [ 9 ] have been investigated. For CO 2 -stimulated systems, a long time and high ventilation are needed [ 31 ]. Light-stimulated systems are difficult to achieve because of the cloudy appearance of the Pickering emulsions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Light-stimulated systems are difficult to achieve because of the cloudy appearance of the Pickering emulsions [ 32 ]. Temperature-stimulated systems are energy-demanding [ 31 ]. Among these stimuli, pH is readily implementable and magnetism is non-invasive and reversible [ 2 , 7 , 10 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%